2022
DOI: 10.48550/arxiv.2202.08223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymptotic safety guaranteed for strongly coupled gauge theories

Andrew D. Bond,
Daniel F. Litim

Abstract: We demonstrate that interacting ultraviolet fixed points in four dimensions exist at strong coupling, and away from large-N Veneziano limits. This is established exemplarily for semisimple supersymmetric gauge theories with chiral matter and superpotential interactions by using the renormalisation group and exact methods from supersymmetry. We determine the entire superconformal window of ultraviolet fixed points as a function of field multiplicities. Results are in accord with the a-theorem, bounds on conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Further, comparing exact results with perturbative ones in regimes where the underlying couplings have become of order unity, it is observed that the latter provides fair estimates in some parameter ranges (i.e. field multiplicities), yet poor estimates in others [39]. We conclude that the size of the perturbative…”
Section: Perturbativitymentioning
confidence: 77%
See 3 more Smart Citations
“…Further, comparing exact results with perturbative ones in regimes where the underlying couplings have become of order unity, it is observed that the latter provides fair estimates in some parameter ranges (i.e. field multiplicities), yet poor estimates in others [39]. We conclude that the size of the perturbative…”
Section: Perturbativitymentioning
confidence: 77%
“…It must be clear, however, that this criterion is not rigorous, and that it should ultimately be confirmed with higher loops or nonperturbatively. Some additional insights are offered by a recent nonperturbative study of asymptotically safe UV fixed points in SU (N ) × SU (M) supersymmetric gauge theories with matter [39], but with significantly simpler superpotentials than the MSSM extensions studied here. There, the method of a-maximisation [40] has been used, giving non-perturbative access to fixed points and chiral superfield anomalous dimensions.…”
Section: Perturbativitymentioning
confidence: 94%
See 2 more Smart Citations
“…We believe that it would be also interesting to generalize the results of this paper to the non-Abelian case. Possibly, they will be also useful for investigating fixed point in supersymmetric theories, see, e.g., [80][81][82] and references therein.…”
Section: Discussionmentioning
confidence: 99%